Semmittevés: Lakótelep és szegénynegyed-mentalitás - Rácz, József (Szociológiai Szemle, 2024)
The author describes the new perspectives on research methods of ethnography. In his own research he conducted investigations among the 16-24-years-old young people of a housing estate, where the field workers adopted the method of participant-observation. In the present study the author describes the everyday activities of the young people, their acts of violence (aggression against persons ad objects), and the connection of the aggression with „doing nothing”. Regarding the group-formation of the young the importance of two factors has been pointed out: the importance of peer-field (which conception is different from that of the peer-group): and the importance of slums mentality.